Characterization of transgene expression and pDNA distribution of the suctioned kidney in mice - Natsuko Oyama; Yuki Fuchigami; Shintaro Fumoto; Megumu Sato; Masayori Hagimori; Kazunori Shimizu; Shigeru Kawakami (Taylor & Francis Group, 2017)
We have previously developed an efficient and safe transfection method for the kidney in mice: renal suction-mediated transfection. In this study, we verified the detailed characteristics of transgene expression and plasmid DNA (pDNA) in mice to develop therapeutic strategies and application to gene function analysis in the kidney. After naked pDNA was administered intravenously, the right kidney was immediately suctioned by a tissue suction device. We examined the spatial distribution of transgene expression and pDNA in the suctioned kidney using tissue clearing by CUBIC, ClearT2, and Scale SQ reagents. Spatial distribution analysis showed that pDNA was transfected into extravascular cells and sufficiently delivered to the deep renal cortex. In addition, we revealed that transgene expression occurred mainly in peritubular fibroblasts of the suctioned kidney by tissue clearing and immunohistochemistry. Next, we confirmed the periods of pDNA uptake and activation of transcription factors nuclear factor-κB and activator protein 1 by luciferase assays. Moreover, the use of a pCpG-free plasmid enabled sustained transgene expression in the suctioned kidney. In conclusion, analyses of the spatial distribution and immunostaining of the section suggest that pDNA and transgene expression occurs mainly in peritubular fibroblasts of the suctioned kidney. In addition, we clarified some factors for efficient and/or sustained transgene expression in the suctioned kidney.